Comparative avifaunal richness and diversity in invasive Acacia dealbata patches and adjacent montane grasslands. Issue 1 (2nd January 2022) - Seath, Jessica; Shackleton, Charlie
Abstract : Invasive alien species are regarded as the second greatest threat to biodiversity globally. Yet, at a local scale their effects may vary, underlying the requirement for more local-scale studies across taxa and settings. Here we consider the effects of an alien invasive tree ( Acacia dealbata, 5–8 m tall) on avifaunal numbers, richness and diversity in A. dealbata patches of three sizes relative to adjacent montane grasslands. Analysis of historical aerial photographs showed that A. dealbata first occurred in the area in the late 1930s/early 1940s and has continued to spread, despite some efforts by the landowner to keep it in check. It now covers approximately 11% of the site. This has provided habitat for a number of bird species more characteristic of wooded vegetation types. The number, richness and diversity of birds were greater in A. dealbata patches than the adjacent grasslands of equivalent size. These measures increased with increasing patch size, but more rapidly for A. dealbata patches than grassland ones. Only six of the 48 species of birds recorded were common between the two vegetation types. The most common feeding guild in the A. dealbata patches was insectivores, whereas in the grasslands it was omnivores. Although the invasion of A. dealbata has added to the habitat diversity of the area, thereby facilitating increased avifaunal diversity, if it continues to spread, then the populations and perhaps richness of grassland birds are likely to be negatively affected.